Análise de medidas mitigadoras para a redução da tensão de restabelecimento transitória em disjuntores de alta tensão: um estudo de caso - (:unkn) unknown (Universidade Federal do Pampa, 2022)
This work presents a study of the behavior of the Transient Recovery Voltage (TRV) in high voltage circuit breakers and the relevant aspects that must be evaluated for the application of mitigating measures to adjust the requests above the admissible limits. TRV is characterized by being an electromagnetic transient that arises between the poles of the terminals of a circuit breaker, when the terminals are opened, due to a fault in the system. At this moment, an electric arc appears between the equipment terminals, which will only be interrupted when the instantaneous value of the electric current tends to zero. At this point, the phenomenon called TRV occurs. The circuit breaker is considered to have been overcome by means of the TRV as soon as its respective thermal and dielectric values are extrapolated, either by the peak value of the TRV, or by its growth rate (RRRV), in accordance with regulations established by technical standards. The results of the analysis of overcoming TRV and RRRV of this work were obtained through simulations in the ATP software, through specific routines for the extraction of these values, which were based on the IEEE C37.06-2009 standard, for nominal capacities of 100 and 30 percent test duty for ungrounded three-phase and phase-to-ground short circuits. The results obtained showed that the insertion of opening resistors in parallel with the main chamber of the circuit breaker resulted in the reduction of the peak value of the TRV, and it was also observed that the introduction of capacitive surge cells significantly reduced the growth rate of the TRV. Keywords: High voltage circuit breaker, transient recovery voltage (TRV), mitigating measures, electromagnetic transient.
Keywords: Engenharia elétrica; Sistemas de energia elétrica; Tensão de restabelecimento transitória TRT; Electrical engineering; Electric power systems; Transient recovery voltage TRV; CNPQ::ENGENHARIAS